Internal Control Enterprise Accounting Problems and Countermeasures Analysis - Song, Zhiyu (Journal of Theory and Practice of Management Science, 2023)
The internal accounting work of enterprises has a significant impact on the development of enterprises. Many enterprises because of internal accounting work there are many deficiencies, caused more serious economic problems. Therefore, it is necessary for relevant personnel to take measures to solve the shortcomings of enterprise accounting work, to promote the smooth development of enterprises.